Immunoregulatory Role of NK Cells in Tissue Inflammation and Regeneration - Tosello-Trampont, Annie; Surette, Fionna A.; Ewald, Sarah E.; Hahn, Young S. (Frontiers in Immunology, 2017)
NK cells represent an important first line of defense against viral infection and cancer and are also involved in tissue homeostasis. Studies of NK cell activation in the last decade have revealed that they are able to respond to the inflammatory stimuli evoked by tissue damage and contribute to both progression and resolution of diseases. Exacerbation of the inflammatory response through interactions between immune effector cells facilitates the progression of non-alcoholic fatty liver disease (NAFLD) into steatosis, cirrhosis, and hepatocellular carcinoma. When hepatic damage is incurred, macrophage activation is crucial for initiating crosstalk with neighboring cells present in the liver, including hepatocytes and NK cells, and the importance of this interaction in shaping the immune response in liver disease is increasingly recognized. Inflicted structural damage can be in part regenerated via the process of self-limiting fibrosis, though persistent hepatic damage will lead to chronic fibrosis and loss of tissue organization and function. The cytotoxic activity of NK cells plays an important role in inducing hepatic stellate cell apoptosis and thus curtailing the progression of fibrosis. Alternatively, in some diseases such as hepatocellular carcinoma (HCC), NK cells may become dysregulated, promoting an immunosuppressive state where tumors are able to escape immune surveillance. This review describes the current understanding of the contributions of NK cells to tissue inflammation and metabolic liver diseases and the ongoing effort to develop therapeutics that target the immunoregulatory function of NK cells.